The Market Performance of Conglomerate Firms in the United Kingdom - Firth, Michael (The Review of Economics and Statistics, 1979)
In the 1960s and early 1970s many conglomerate companies were treated as the glamour shares of the stock market and they traded at high price-earnings ratios. One reason for this glamour status was the belief that these conglomerates had dynamic, entrepreneurial management and when this was injected into taken-over firms greatly increased efficiency and profits would ensue, which would ultimately be reflected in a superior share price performance. The current note examines this hypothesis by presenting the results of a research study into the actual stock market performance of conglomerate firms in the United Kingdom. Following Professors Weston, Smith and Shrieves (this REVIEW, 1972) the study uses a capital asset pricing model approach in measuring performance . Contrary to Weston et al. 's findings the current study found that conglomerates did not display superior risk-adjusted stock market performance. The findings are consistent, however, with other studies in the United States (Melicher and Rush, 1973; Brenner and Downes, 1979), as well as with previous studies into takeovers in Britain (Firth, 1976 and 1979) which showed no stock market gains resulting from making acquisitions.